Phylogeny of the genus Caledonica (Coleoptera: Cicindelinae) - Kudrna, Arnošt (Jihočeská univerzita, 2019)
Phylogeny of the New Caledonian tiger beetle genus Caledonica is reconstructed using three phylogenetic trees.Brief description of New Caledonian habitats, geography and geological history are presented and results are discussed.
Phylogeny of the genus Caledonica(Coleoptera: Cicindelinae)
Keywords: Coleoptera; Phylogeny; New Caledonia; Coleoptera; Phylogeny; New Caledonia